The effectiveness of nicotine replacement therapy during pregnancy: investigating the role of nicotine substitution, nicotine metabolism and pregnant smokers’ experiences - Bowker, Katharine (2016)
Nicotine replacement therapy (NRT) is effective in non-pregnant populations at assisting smoking cessation, but there is no evidence that NRT can help pregnant smokers to stop. Nicotine metabolism increases during pregnancy, and so the nicotine dose delivered by NRT could be insufficient for ameliorating withdrawal symptoms. However, little is known about the level of nicotine substitution provided by NRT or the pattern of nicotine metabolism during pregnancy. Also low adherence to NRT may explain why NRT does not appear to be effective.